Econophysics Approaches to Large-Scale Business Data and Financial Crisis - Takayasu, Misako; Watanabe, Tsutomu; Takayasu, Hideki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
The new science of econophysics has arisen out of the information age. As large-scale economic data are being increasingly generated by industries and enterprises worldwide, researchers from fields such as physics, mathematics, and information sciences are becoming involved. The vast number of transactions taking place, both in the financial markets and in the retail sector, is usually studied by economists and management and now by econophysicists. Using cutting-edge tools of computational analysis while searching for regularities and (3z(Blaws(3y (Bsuch as those found in the natural sciences, econophysicists have come up with intriguing results. The ultimate aim is to establish fundamental data collection and analysis techniques that embrace the expertise of a variety of academic disciplines. This book comprises selected papers from the international conference on novel analytical approaches to economic data held in Tokyo in March 2009. The papers include detailed reports on the market behavior during the financial crisis of 2008 and discussions on the mechanism of bubbles and crashes, with proposals for avoiding new crises. Filled with up-to-date research, this book will interest researchers and students, finance professionals, and scholars in diverse fields.s
Financial Market Properties -- Trend Switching Processes in Financial Markets -- Nonlinear Memory and Risk Estimation in Financial Records -- Microstructure and Execution Strategies in the Global Spot FX Market -- Temporal Structure of Volatility Fluctuations -- Theoretical Base of the PUCK-Model with Application to Foreign Exchange Markets -- Financial Crisis and Macroeconomics -- Financial Bubbles, Real Estate Bubbles, Derivative Bubbles, and the Financial and Economic Crisis -- Global and Local Approaches Describing Critical Phenomena on the Developing and Developed Financial Markets -- Root Causes of the Housing Bubble -- Reconstructing Macroeconomics Based on Statistical Physics -- How to Avoid Fragility of Financial Systems: Lessons from the Financial Crisis and St. Petersburg Paradox -- General Methods and Social Phenomena -- Data Centric Science for Information Society -- Symbolic Shadowing and the Computation of Entropy for Observed Time Series -- What Can Be Learned from Inverse Statistics? -- Communicability and Communities in Complex Socio-Economic Networks -- On World Religion Adherence Distribution Evolution.
Keywords: Physics; Data mining; Economics -- Statistics; Econometrics; Physics; Statistical Physics, Dynamical Systems and Complexity; Econometrics; Statistics for Business/Economics/Mathematical Finance/Insurance.; Data Mining and Knowledge Discovery